One-Step Reverse-Transcription Recombinase Polymerase Amplification Using Lateral Flow Strips for the Detection of Coxsackievirus A6 - Xie, Jia; Yang, Xiaohan; Duan, Lei; Chen, Keyi; Liu, Pan; Zhan, Wenli; Zhang, Changbin; Zhao, Hongyu; Wei, Mengru; Tang, Yuan; Luo, Mingyong (Frontiers in Microbiology, 2021)
Hand, foot, and mouth disease (HFMD) is a common infectious disease affecting mainly children under five years of age. Coxsackievirus A6 (CVA-6), a major causative pathogen of HFMD, has caused outbreaks in recent years. Currently, no effective vaccine or antiviral treatments are available. In this study, one-step reverse-transcription recombinase polymerase amplification (RT-RPA), combined with a disposable lateral flow strip (LFS) assay, was developed to detect CVA-6. This assay can be performed in less than 35 min at 37°C without expensive instruments, and the result can be observed directly with the naked eye. The sensitivity of the RT-RPA-LFS was 10 copies per reaction, which was comparable to that of the conventional real-time quantitative polymerase chain reaction (qPCR) assays. Moreover, the assay specificity was 100%. The clinical performance of the RT-RPA-LFS assay was evaluated using 142 clinical samples, and the coincidence rate between RT-RPA-LFS and qPCR was 100%. Therefore, our RT-RPA-LFS assay provides a simple and rapid approach for point-of-care CVA-6 diagnosis.